Beyond the moral domain: The normative sense among the Chinese - Berniūnas, Renatas; Silius, Vytis; Dranseika, Vilius (Psichologija, 2020)
In this paper we report a study on how different types of normatively relevant transgressions are evaluated by Chinese participants. We hypothesized that, given the continuing influences of Confucian worldview on contemporary Chinese societies, the Chinese will not make a distinction between moral (daode) and conventional norms of cultured behavior (wenming). Our results indicate that Chinese participants expressed a strong normative conviction not only towards harmful and unfair actions, usually subsumed under the moral domain in Western literature, but also towards violations of what would be widely accepted as conventional (or cultural) norms. Similarly, Chinese participants expressed a strong normative conviction towards violations of the traditional Chinese value of family reverence (xiao), thus further supporting our general thesis. Moreover, results indicate that, overall, explicit considerations of wenming (unculturedness) emerged as the best predictor of a normative conviction response among the Chinese. Though considerations of harm and fairness also emerged as significant predictors of normative conviction response. The results are discussed in the light of recent debates about the moral/conventional distinction and the scope of morality.
Keywords: moral/conventional distinction; normative cognition; cross-cultural research; China; moral domain